Evaluation of bacterial colonization and bacteriuria secondary to internal ureteral stent - Rahman, AA; Alam, MM; Shamsuzzaman, SM; Haque, ME (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Jul;19(2):366-71 The abstract of this article is available on the PubMed website